(untitled) (Global Journal of Medical Research, 2023)
Introduction This paper will cover new updates on atopic dermatitis as a chronic and inflammatory condition that affects people of all ages but is most common in children Its etiology involves genetic immunological and environmental factors with risk factors such as maternal exposure during pregnancy irritants climate change pollution and more Methodology The current study is a literature review the database of which was taken from the SciELO Scientific Electronic Library Online and PubMed platforms Results Atopic dermatitis is a chronic and relapsing disease that affects individuals of all ages but especially children It is an inflammatory condition that has a multifactorial etiology involving genetic immunological and environmental factors that damage the continuity of the epidermis The incidence can vary according to geographical region as well as ethnicity It is generally more common in developed countries with around 15 to 20 of children and 1 to 3 of adults being affected and its growth can be explained by urbanization and pollution added to the context which are significant risk factors for this condition 1